(3TQM GdcGJj Ydi EjSGZhLjs - (3GdcGJj, MSGe GdOjf MSf, J (B760 (3g`s ((3eUWai Hf CMeOs)
(3ChdgG (B:s
(3GdMeO ddg hGLH hLhOg aEf cJGH GdTjN CKjQ GdOjf GdCHgQj GdeTghQ HEjSGZhLj deG cGf Ydi HYV GdENhGf eJYSQG hYdi HYVge eJjSQG CQOJ Cf GcJH HGdJeGSge ChQGbG dJRjd JYSQgs
(3BNQgG (B:s
(3ceG Jbhd gPG GdLSe EeG TLQ Ch MLQ dcfg TLQ adjS HMLQ hdcfg MLQ adjS HTLQ Ch eQcH ef efaUdI GdeGfYI GdNdh eY QaY CMO GdLRFjf hfJjLJg hVY GdLRA GdBNQ hfJjLJg GKfGf CjVG JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1/579s
(3cTa GdXfhf (B1\206s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs